Efficacy and safety of lenvatinib versus sorafenib in first-line treatment of advanced hepatocellular carcinoma: A meta-analysis - Luo, Jia; Gao, Benjian; Lin, Zhiyu; Fan, Hua; Ma, Wen; Yu, Danfei; Yang, Qian; Tian, Jing; Yang, Xiaoli; Li, Bo (Frontiers in Oncology, 2022)
Abstract Objective: Lenvatinib and sorafenib are first-line oral multikinase inhibitors approved for the treatment of advanced hepatocellular carcinoma (HCC). However, the choice of the primary therapeutic agent among these two remains controversial. This meta-analysis aimed to estimate the efficacy and safety of lenvatinib and sorafenib in patients with advanced HCC. Methods: PubMed, Cochrane Library, Web of Science, and Embase databases were searched for relevant research published up to June 30, 2022. After quality assessment and data extraction of the included studies, RevMan 5.3 software was used for analysis. Odds ratio (OR) and hazard ratio (HR) with a 95% confidence interval (CI) were calculated using a fixed-effects or random-effects model. Results: Fifteen studies containing 3908 patients were included after final scrutiny. Our meta-analysis showed that there was no significant difference in overall survival (OS) between the lenvatinib and sorafenib groups (HR = 0.86; 95% CI: 0.72–1.02; p = 0.09); however, the progression-free survival (PFS) (HR = 0.63; 95% CI: 0.53–0.74; p < 0.00001), complete response (CR) (OR = 5.61; 95% CI: 2.71–11.64; p < 0.00001), partial response (PR) (OR = 4.62; 95% CI: 3.06–6.98; p < 0.00001), objective response rate (ORR) (OR = 5.61; 95% CI: 3.90–8.09; p < 0.00001), and disease control rate (DCR) (OR = 2.42; 95% CI: 1.79–3.28; p < 0.00001) in the lenvatinib group were significantly better than those in the sorafenib group. In terms of treatment safety, lenvatinib had similar incidences of any grade adverse events (AEs) (OR = 0.99; 95% CI: 0.47–2.09; p = 0.98) and grade ≥ 3 AEs (OR = 1.17, 95% CI; 1.00–1.37; p = 0.05) compared to sorafenib. Besides, lenvatinib was significantly associated with a higher incidence of hypertension, proteinuria, fatigue, decreased appetite, and weight loss, whereas sorafenib was associated with a higher incidence of diarrhea and hand-foot skin reaction (p < 0.05). Conclusion: Given its potential survival benefit and good tolerability, lenvatinib is an appropriate and promising alternative to sorafenib as first-line systemic therapy in patients with advanced HCC.